Pemerolehan Fonologi Anak Usia Dini dalam Pengucapan Fonem saat Berkomunikasi: Kajian Psikolinguistik - Olivia Ananda; Abelia Nur Hikmah; Fatimiyah Ratu Izzahroh; Hodairiyah Hodairiyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to describe early childhood phonological acquisition of phoneme pronunciation when communicating based on psycholinguistic studies. Language acquisition in children occurs naturally based on interaction with the environment and one of the aspects that develops first is phonology, namely the ability to recognize, understand and produce language sounds. This research uses a qualitative descriptive approach with a case study method. The research data is in the form of oral speech from early childhood obtained through listening and note-taking techniques in the context of everyday communication. Data analysis focused on the forms of phoneme changes that appeared in children's speech. The research results show that there are two dominant forms of phonological change, namely phoneme deletion and phoneme replacement. Phoneme deletions are found in the words nose which are pronounced as idung and mother as unda. Meanwhile, many phoneme changes occur in the /r/ phoneme which changes to /l/, /y/, and /n/, such as in the words house becomes luma, stomach becomes peyut, and neck becomes lehen. Apart from that, the phoneme /s/ also changes to /t/, as in the word one which is pronounced tatu and big becomes betan. Research findings show that the phonemes /r/ and /s/ are the phonemes that change most frequently because of their relatively high level of articulation difficulty. Based on psycholinguistic studies, these changes are part of the normal phonological acquisition process and reflect the gradual development of children's language abilities. As age increases and interaction with the environment increases, children's ability to pronounce phonemes will develop towards the form of language used by adult speakers